Kepastian Hukum Terhadap Ancaman Non-Verbal Sebagai Tindak Pidana kekerasan Dalam Pasal 335 KUHP (Studi Kasus Putusan 1035/PID.B/2024/PN SBY) - Heru Herlambang; Siti Marwiyah; Wahyu Prawesthi (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2026)
This research examines legal certainty regarding non-verbal threats as a criminal act of violence under Article 335 of the Indonesian Criminal Code (KUHP) by analyzing Decision Number 1035/Pid.B/2024/PN Sby as a case study. The issue arises from the absence of a clear normative definition of non-verbal threats, such as body gestures or movements that appear intimidating without physical contact. In judicial practice, such actions are often interpreted as threats of violence, raising concerns related to legal certainty, the principle of legality, the doctrine of lex certa, and the protection of the defendant’s rights. This study aims to analyze whether Indonesian criminal law provides clear legal guidelines for determining when non-verbal conduct can be classified as a threat of violence under Article 335 of the Criminal Code. It also examines the implications of this normative ambiguity on legal certainty and the protection of defendants’ rights within judicial practice. The research employs a normative legal method using statutory, conceptual, and case approaches. Legal materials are analyzed qualitatively through normative interpretation and jurisprudential examination. The results show that Article 335 of the Criminal Code does not provide clear parameters for assessing non-verbal threats as threats of violence. This lack of clarity creates broad interpretative discretion for law enforcement and potentially leads to subjective judgments and overcriminalization. Criminalizing gestures without physical contact may also contradict the principle of legality, the doctrine of lex certa, and the principle of ultimum remedium in criminal law. Therefore, clearer legal formulations regarding the classification of non-verbal threats are necessary to ensure legal certainty and proportional protection of defendants’ rights in the criminal justice system.